UPAYA PENGURUS ORGANISASI IKATAN PEMUDA MENYADIK DAYAK KANTUK KOTA PONTIANAK DALAM MEMBANGUN SOLIDARITAS MEKANIK - Margareta Mira Peranti; Izhar Salim; Imran Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis article is entitled "The Efforts of the Pontianak City IPMDK Organizational Management Association in Building Mechanic Solidarity". The general problem in this research is "How are the Efforts of the Management of the Pontianak City IPMDK Organization Management in Building Mechanic Solidarity?". The general objective of this research is "To find out the form of division of labor, collective awareness and reprensive law that exists in the IPMDK organization in Pontianak City and the efforts of the management in building mechanical solidarity". The approach used in this research is a qualitative approach with descriptive methods. The data collection techniques used were observation techniques, interview guidelines, and documentation. Sources of data in this study are the Chairperson and Secretary and members of the IPMDK. The results of this study indicate the efforts of the management of the Pontianak City IPMDK Organization in Building Mechanic Solidarity, in the form of division of labor, collective awareness and repressive law.Keywords: Organizational Management Efforts, Mechanical Solidarity